My Spirit Lives - Chinook, Roxanne (Social justice, 2004)
Part of a special issue on native women and state violence. The writer gives a personal account of her experiences, since childhood, of sexual victimization and substance abuse, and she discusses the role that her Native American heritage played in her oppression. She describes her struggle to break the vicious cycle of violence, shame, and self-destruction and recounts her journey toward healing and empowerment.